Contextual Interference Effects in Early Assessment: Evaluating the Psychometric Benefits of Item Interleaving - Albano, Anthony D.; McConnell, Scott R.; Lease, Erin M.; Cai, Liuhan (Frontiers in Education, 2020)
Research has shown that the context of practice tasks can have a significant impact on learning, with long-term retention and transfer improving when tasks of different types are mixed by interleaving (abcabcabc) compared with grouping together in blocks (aaabbbccc). This study examines the influence of context via interleaving from a psychometric perspective, using educational assessments designed for early childhood. An alphabet knowledge measure consisting of four types of tasks (finding, orienting, selecting, and naming letters) was administered in two forms, one with items blocked by task, and the other with items interleaved and rotating from one task to the next by item. The interleaving of tasks, and thereby the varying of item context, had a negligible impact on mean performance, but led to stronger internal consistency reliability as well as improved item discrimination. Implications for test design and student engagement in educational measurement are discussed.